2019
DOI: 10.1002/bit.27135
|View full text |Cite
|
Sign up to set email alerts
|

In vivo surveillance and elimination of teratoma‐forming human embryonic stem cells with monoclonal antibody 2448 targeting annexin A2

Abstract: This study describes the use of a previously reported chimerised monoclonal antibody (mAb), ch2448, to kill human embryonic stem cells (hESCs) in vivo and prevent or delay the formation of teratomas. ch2448 was raised against hESCs and was previously shown to effectively kill ovarian and breast cancer cells in vitro and in vivo. The antigen target was subsequently found to be Annexin A2, an oncofetal antigen expressed on both embryonic cells and cancer cells. Against cancer cells, ch2448 binds and kills via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…AnxA2 antibody-conjugated and curcumin-loaded nanoparticles effectively accumulated in tumours, providing sustained release of curcumin with potential to reduce metastatic breast cancer progression [ 163 ]. A monoclonal AnxA2 antibody not only allowed monitoring EMT in breast and ovarian cancers, but also provided antibody-dependent cell toxicity and efficient killing when conjugated to cytotoxic drugs and expressed as a chimeric immunoglobulin G1 [ 164 , 165 , 166 ]. Other beneficial effects of AnxA2 antibodies include the inhibition of neoangiogenesis in TNBC xenograft models, which involves reduced plasmin generation as well as loss of AnxA2 tyrosine 23 phosphorylation [ 167 , 168 ].…”
Section: Anxa2mentioning
confidence: 99%
“…AnxA2 antibody-conjugated and curcumin-loaded nanoparticles effectively accumulated in tumours, providing sustained release of curcumin with potential to reduce metastatic breast cancer progression [ 163 ]. A monoclonal AnxA2 antibody not only allowed monitoring EMT in breast and ovarian cancers, but also provided antibody-dependent cell toxicity and efficient killing when conjugated to cytotoxic drugs and expressed as a chimeric immunoglobulin G1 [ 164 , 165 , 166 ]. Other beneficial effects of AnxA2 antibodies include the inhibition of neoangiogenesis in TNBC xenograft models, which involves reduced plasmin generation as well as loss of AnxA2 tyrosine 23 phosphorylation [ 167 , 168 ].…”
Section: Anxa2mentioning
confidence: 99%
“…Simeon Cua and his colleagues generate a mAb, IgG1 2448, targeting a unique glycan epitope on ANXA2. It demonstrated good anti-tumor efficacy in vivo and indicated that 2448 can be a potential candidate of targeted therapy for ovarian and breast cancer [132,133].…”
Section: Annexin A2 Is a Potential Therapeutic Target For Cancersmentioning
confidence: 99%
“…Recently, our group proposed a strategy to complement existing methods that eliminate teratoma-forming cells in vitro [50]. Residual undifferentiated PSCs could possibly escape in vitro removal methods and be introduced into patients together with the differentiated cells.…”
Section: Mabs For Regenerative Cell Therapymentioning
confidence: 99%
“…Another hESC mAb, 2448, binds to annexin A2 on hESCs and on cancer cells [34,50]. Cua et al showed that the mAb binds to glycans on annexin A2, which confers the mAb a unique property.…”
Section: Mabs For Oncologymentioning
confidence: 99%